Design, Modelling, and Simulation of Francis Water Turbine for Cisomang Water Power Plant with Head of 131,07 m and Discharge of 1,61 m3/s - KURNIAWAN (NIM : 13113108), JULIO
Nowadays, electricity has become the primary needs in every activities, especially for those who live in urban areas. Electricity consumption in Indonesia keeps increasing every year, and the trend will likely to set in the long run. Therefore, it has to be balanced with equal production of electricity, and if possible, by using renewable energy as the main source. The 35000 MW Project has officially started, hoping that this could be the answer to the electricity needs. Power plants have been built, with some of it is a water power plant type. The type of turbine suitable for water power plant is Francis turbine. For that reason, designing for turbine in Cisomang water power plant needs to be done, so the needs for electricity can be fulfilled. In this final project, numerical study has been done on Francis turbine. Design data is stated for discharge of 1,61 m3/s, head of 131,07 m, and rotational speed of 1000 rpm. Each part of turbine including runner, spiral casing, draft tube, and guide vane will be designed to make the 3D model. Each model will then be assembled so simulation can be run, with the purpose of finding the operation point based on the specification stated. The simulation is done by varying the angle of guide vane opening to find the operation point. Based on the simulation results, highest mechanic efficiency on operation point is achieved by 16 blade runner with NACA profile, with value of 88,24 %, output power of 1789,25 kW on 19o opening angle, producing discharge of 1,617 m3/s. Pressure contour results show that the lowest pressure present is 10315 Pa, and with the vapour water pressure value of 3169 Pa in 25oC, so that cavitation does not occur in the runner.